PENINGKATAN HASIL BELAJAR SISWA KELAS IV TEMA 6 CITA-CITAKU MELALUI PENERAPAN MODEL DEMONSTRATION DI SD 01 GULANG - Nikmatul Khusnah; Deka Setiawan; Santoso Santoso (Fakultas Keguruan dan Ilmu Pendidikan, 2022)
This Classroom Action Research is motivated by the low learning outcomes of students in Indonesian and PPKn lessons. This research is in the form of classroom action research, by adapting the model of Classroom Action Research by Kemmis, and Mc. Taggart. This Classroom Action Research was conducted through two cycles. The stages in this classroom action research are (1) action planning, (2) action implementation, (3) observation, and (4) reflection. The research subjects in this Classroom Action Research, namely grade IV SD 01 Gulang, Mejobo District, Kudus Regency, with a total of 32 students, consisting of 12 male students, and 20 female students, and a fourth grade teacher. The assessment instrument used in this Classroom Action Research is an assessment for work learning outcomes. The results of this Classroom Action Research are the researchers using the demonstration method through the Puzzle media which will be used in the learning process. So the use of the demonstration method through puzzle media on the theme 6 My Goals can improve student learning outcomes in grade IV SD 01 Gulang Mejobo Kudus